Finding the Correct Partner: The Meiotic Courtship - Tomás Naranjo (Scientifica)
Homologous chromosomes are usually separated at the entrance of meiosis; how they become paired is one of the outstanding mysteries of the meiotic process. Reduction of spacing between homologues makes possible the occurrence of chromosomal interactions leading to homology detection and the formation of bivalents. In many organisms, telomere-led chromosome movements are generated that bring homologues together. Additional movements produced by chromatin conformational changes at early meiosis may also facilitate homologous contacts. Organisms used in the study of meiosis show a surprising variety of strategies for homology detection. In dipterans, homologous chromosomes remain paired throughout most of development. Pairing seems to arise as a balance between promoter and suppressor pairing genes. Some fungi, plants and animals, use mechanisms based on recombinational interactions. Other mechanisms leading to homology search are recombination-independent and require specialized pairing sites. In the worm Caenorhabditis elegans, each chromosome carries a pairing center consisting of a chromosome-specific DNA-protein complex, and in the fission yeast Schizosaccharomyces pombe, the sme2 locus encodes a meiosis-specific non-coding RNA that mediates on homologous recognition. In addition, mismatch correction plays a relevant role, especially in polyploids, which evolved genetic systems that suppress pairing between non-homologous related (homoeologus) chromosomes.